A study of mobile banking adoption among university students - Farah Dhiba, Abd Aziz (2020)
The main objective of this study is to investigate factors that can predict the adoption of mobile banking in Malaysia. This research also investigates the mediating role of hedonic motivation between mobile banking and its predictor: hedonic motivation, perceived ease of use, perceived usefulness, perceived compatibility, and perceived complexity. Inconsistency of finding in the past literature between the relationship of adoption of mobile banking and its determinant has driven the researcher to explain the inconsistencies. Survey questionnaires were distributed using an online questionnaire to the undergraduate students of Universiti Utara Malaysia. 386 usable questionnaires used for the analysis. The direct and indirect relationship has been analyzed by using the PLS-SEM method. The results show that hedonic motivation, perceived usefulness, perceived compatibility, and perceived complexity has a significant relationship to the adoption of mobile banking while perceived ease of use is found to be insignificant. For the indirect relationship, the results show that hedonic motivation mediates the relationship between perceived usefulness, perceived compatibility, and perceived complexity to the adoption of mobile banking, and hedonic motivation found out that it did not mediate the relationship between perceived ease of use and adoption of mobile banking. Finally, managerial implications, limitations of the study, and recommendations of future research are discussed.